2020
DOI: 10.1007/s11618-020-00957-7
|View full text |Cite
|
Sign up to set email alerts
|

Stichwort: Überzeugungen von Lehrkräften im Kontext migrationsbezogener Heterogenität

Abstract: Zusammenfassung In Deutschland leben Menschen aus über 150 verschiedenen Ländern. Fast jedes dritte Kind in der Schule hat Eltern, von denen mindestens ein Elternteil in einem anderen Land geboren wurde. Lehrkräften und ihren migrationsbezogenen Überzeugungen kommt in diesem Kontext eine besondere Rolle zu, weshalb sie in den letzten 20 Jahren in den Fokus verschiedener Forschungsbemühungen in Deutschland gerückt sind. Der vorliegende Beitrag stellt diese anhand eines integrativen Reviews entlang von vier Schw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…The perceived low stress caused by the cultural heterogeneity of the students can be attributed to professional training, for example on intercultural competence, or to a generally more open attitude of the teachers toward immigration and immigrants (cf. Civitillo et al, 2019 ; Gebauer and McElvany, 2020 ; Hachfeld and Syring, 2020 ). The latter is also true of the teachers interviewed here, hardly any of whom saw immigration exclusively as a problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The perceived low stress caused by the cultural heterogeneity of the students can be attributed to professional training, for example on intercultural competence, or to a generally more open attitude of the teachers toward immigration and immigrants (cf. Civitillo et al, 2019 ; Gebauer and McElvany, 2020 ; Hachfeld and Syring, 2020 ). The latter is also true of the teachers interviewed here, hardly any of whom saw immigration exclusively as a problem.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, multicultural beliefs are important for teaching students with a migration background and dealing with cultural heterogeneity: “teachers with multicultural beliefs can be expected to incorporate students' different cultures into everyday school practice when planning their lessons, choosing materials, and interacting with students in class” (Hachfeld et al, 2011 , p. 987). Multicultural beliefs can reduce prejudice and promote self-efficacy, enthusiasm, self-reflection, and culturally responsive teaching (Hachfeld et al, 2011 , 2012 ; Civitillo et al, 2019 ; Gebauer and McElvany, 2020 ; Hachfeld and Syring, 2020 ; Abacioglu et al, 2022 ), which in turn can reduce strain and burnout (Gutentag et al, 2018 ; Strasser, 2021 ). There is little evidence regarding teachers' attitudes toward refugees (e.g., Terzi et al, 2019 ; Chwastek et al, 2021 ).…”
Section: Target Group-specific Professional Knowledge Of Teachersmentioning
confidence: 99%
“…B. Avalos, Zisselsberger, Langer-Osuna & Secado, 2015;Benholz & Siems, 2016;Darsow, Wagner & Paetsch,2 017a;G ültekin et al,2 016;Hachfeld, 2012;Michalak,2012;Ohm,2009).…”
Section: 3unclassified
“…Most quantitative empirical studies on teachers' cultural beliefs focus on the link with teachers' self-reported proficiency to teach in culturally diverse classrooms (for a review for the German context, see Hachfeld & Syring, 2020). Results indicate that pre-service and in-service teachers who endorse multicultural beliefs are particularly enthusiastic about teaching immigrant students and report high levels of self-efficacy in doing so (Gutentag et al, 2017;Hachfeld et al, 2015).…”
Section: Empirical Findings On the Relationship Between Teachers' Cultural Beliefs And Students' School Adaptationmentioning
confidence: 99%